Biochanin A Inhibits the Growth and Biofilm of Candida Species - Monika Janeczko; Elżbieta Kochanowicz (MDPI AG, 2024)
The aim of this study was to investigate the antifungal activity of biochanin A (BCA) against planktonic growth and biofilms of six Candida species, including C. albicans, C. parapsilosis, C. glabrata, C. tropicalis, C. auris, and C. krusei. We applied various assays that determined (a) the antimicrobial effect on growth of Candida species, (b) the effect on formation of hyphae and biofilm, (c) the effect on the expression of genes related to hyphal growth and biofilm formation, (d) the influence on cell wall structure, and (e) the effect on cell membrane integrity and permeability. Moreover, disk diffusion tests were used to investigate the effect of a combination of BCA with fluconazole to assess their possible synergistic effect on drug-resistant C. albicans, C. glabrata, and C. auris. Our results showed that the BCA MIC50 values against Candida species ranged between 125 µg/mL and 500 µg/mL, and the MIC90 values were in a concentration range from 250 µg/mL to 1000 µg/mL. The treatment with BCA inhibited adhesion of cells, cell surface hydrophobicity (CSH), and biofilm formation and reduced hyphal growth in all the analyzed Candida species. Real-time qRT-PCR revealed that BCA down-regulated the expression of biofilm-specific genes in C. albicans. Furthermore, physical destruction of C. albicans cell membranes and cell walls as a result of the treatment with BCA was observed. The combination of BCA and fluconazole did not exert synergistic effects against fluconazole-resistant Candida.